(3GdJaQjY aj GdeSGFd Ydi ePgH GdEeGe eGdcs - (3CHh GdbGSe YHjO Gddg Hf GdMSf Hf GdMSjf Hf GdLdGH GdHZOGOjs ((3CMeO Hf eMeO Hf YGeQ Hf WQNGf GdJGLQ s)
(3ChdgG (B:s
(3cJGH GdfcGM s
(3BNQgG (B:s
(3hdG HCS Cf jQbi GdPei GdeSde HcJGH Gddg YR hLd hCSeGFg Je GdLRA GdKGfi ef cJGH GdJaQjY , hHJeGeg Je LejY cJGH GdLdGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdePGgH (B496) s
Keywords: (3abg GdePGgH GdCNQis